Central Mucoepidermoid Carcinoma of Mandible. A Case Report and Literature Review - Mohamed Elarabi,; Lubna Azzuz,; Subhashraj Krishnaraaj, (Journal of Orofacial Research, 2021)
Central mucoepidermoid carcinoma (CMC) is a rare lesion seen in the maxillofacial region. It is frequently seen in the mandible,especially the posterior than in the anterior region. Since the pathogenesis is not well explored in the past and the variations inthe clinical presentation, the diagnosis of this lesion can be challenging. We report an extremely unusual case of a CMC in thepremolar region of the mandible of a 47-year-old male patient. The clinical, radiological presentation and the surgicalmanagement of the tumor along with the reconstructive techniques utilized to restore the mandible. Although CMC is an unusualtumor of the jaws, it can be locally aggressive, but if treated with wide surgical excision it has a good prognosis. The patient wasunder follow-up and had not shown any signs of recurrence 2 years after surgery.